Pengembangan Tes Diagnostik pada Materi Redoks sebagai Tes Penempatan dengan Model Pembelajaran Sorogan-Bandongan - Maslahatul Ummah; Rinaningsih (UNIB Press, 2026)
This study aimed to develop a diagnostic test instrument on redox reactions to serve as a placement test for the Sorogan-Bandongan learning model. The study employed the Research and Development (R&D) method, following procedures that included a needs assessment, instrument development, expert validation, revision, and testing. The instrument, consisting of 25 multiple-choice questions, demonstrated a content validity of 0.91 and a construct validity of 0.92. Trial results involving 30 students indicated that all test items were valid, with a Cronbach’s Alpha reliability coefficient of 0.933. The instrument also exhibited good to excellent discrimination power and a moderate difficulty level. Based on these results, the instrument is deemed valid, reliable, and suitable for use as a placement test to identify students' prior knowledge within the Sorogan-Bandongan learning model.